An optimal allocation strategy for GFM and GFL converters considering transient voltage stability constraints - LI Qun; TANG Weijia; WANG Chenggen; ZHANG Sen (Zhejiang dianli)
The hybrid grid-forming （GFM） and grid-following （GFL） converter integration systems combine the technical advantages of GFM voltage sources and GFL current sources. However， in weak power grids， the transient period of the GFL inverter is prone to transient voltage instability caused by the phase-locked loop （PLL）. To address this， the paper proposes an optimal allocation strategy for GFM and GFL inverters， taking into account transient voltage stability constraints in weak grids. First， the control system architecture and transient voltage characteristics of both GFM and GFL inverters are introduced. Next， the essence of transient instability of the PLL in weak grids is analyzed. Third， it is suggested utilizing GFM inverters as internal voltage sources for new energy stations and derive an optimal allocation strategy for GFM inverters within the new energy system. This strategy ensures PLL stability for GFL inverters under transient conditions， leveraging the advantages of GFM voltage support in the initial transient phase and GFL voltage support during the transient stability. This enables new energy stations to provide active， rapid， and effective support for transient voltage stability. Finally， the effectiveness and practicality of the proposed strategy is validated through simulations of the hybrid GFM and GFL converter integration systems.